Distribution of the Mycobacterium community and polycyclic aromatic hydrocarbons (PAHs) among different size fractions of a long‐term PAH‐contaminated soil - Maarten Uyttebroek; Philip Breugelmans; Mieke Janssen; Pierre Wattiau; Boris Joffe; Ulrich Karlson; Jose‐Julio Ortega‐Calvo; Leen Bastiaens; Annemie Ryngaert; Martina Hausner; Dirk Springael (Environmental Microbiology, 2006)
Summary Mycobacterium is often isolated from polycyclic aromatic hydrocarbon (PAH)‐contaminated soil as degraders of PAHs. In model systems, Mycobacterium shows attachment to the PAH substrate source, which is considered to be a particular adaptation to low bioavailability as it results into increased substrate flux to the degraders. To examine whether PAH‐degrading Mycobacterium in real PAH‐contaminated soils, in analogy with model systems, are preferentially associated with PAH‐enriched soil particles, the distribution of PAHs, of the PAH‐mineralizing capacity and of Mycobacterium over different fractions of a soil with an aged PAH contamination was investigated. The clay fraction contained the majority of the PAHs and showed immediate pyrene‐ and phenanthrene‐mineralizing activity upon addition of 14 C‐labelled pyrene or phenanthrene. In contrast, the sand and silt fractions showed a lag time of 15–26 h for phenanthrene and 3–6 days for pyrene mineralization. The maximum pyrene and phenanthrene mineralization rates of the clay fraction expressed per gram fraction were three to six times higher than those of the sand and silt fractions. Most‐probable‐number (MPN)‐polymerase chain reaction demonstrated that Mycobacterium represented about 10% of the eubacteria in the clay fraction, while this was only about 0.1% in the sand and silt fractions, indicating accumulation of Mycobacterium in the PAH‐enriched clay fraction. The Mycobacterium community composition in the clay fraction represented all dominant Mycobacterium populations of the bulk soil and included especially species related to Mycobacterium pyrenivorans , which was also recovered as one of the dominant species in the eubacterial communities of the bulk soil and the clay fraction. Moreover, Mycobacterium could be identified among the major culturable PAH‐degrading populations in both the bulk soil and the clay fraction. The results demonstrate that PAH‐degrading mycobacteria are mainly associated with the PAH‐enriched clay fraction of the examined PAH‐contaminated soil and hence, that also in the environmental setting of a PAH‐contaminated soil, Mycobacterium might experience advantages connected to substrate source attachment.